Komunikasi Inovasi Jasa Raharja Cabang Riau Dalam Mengimplementasikan Pelayanan Santunan Online Korban Kecelakaan Di Kota Pekanbaru - Sinta Sinta; Suyanto Suyanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Innovation communication is a way of conveying the discovery of new ideas to society so that social change occurs. A new innovation that is a solution to Jasa Raharja services which is caused by the high number of accidents in Pekanbaru City. In-person support services take a lot of time and take a long time, online updates make it easier for users of these support services. This research aims to analyze the communication innovation of raharja services in implementing online compensation services for accident victims in Pekanbaru city. This research uses qualitative research methods, with data collection techniques using interviews and analyzing the media used in the innovation diffusion process. As for determining research subjects, a purposive technique was used with five informants, then the data analysis technique used Miles and Huberman data analysis techniques which included data collection, data reduction, data presentation and conclusion drawing. This research uses Rogers and Shoemaker's theory of diffusion of innovation. This theory examines messages in the form of new ideas or thoughts, which cause social change.From the research results, this innovation communication has 4 stages, namely. In this research it can be concluded based on the results of the analysis using Roger's theory which has 4 points, This innovation distribution explains that the involvement of communicators provides information in the form of socialization in the form of a content that states information about how to claim or submit compensation from Jasa Raharja. A communicator does not only work alone, this communicator is the Head of Public Relations, Jasa Raharja, who works together with the compensation service staff to collaborate with the community to make it easier and more affordable. With new innovations, since 2009, compensation services for accident victims have gone from conventional forms to online services. This communication channel uses social media, namely in the form of Instagram and Tik Tok, then uses print media, television media and radio media. By implementing the Innovation Division, it has made progress, but of course there are still new innovations, of course this is influenced by factors that hinder the establishment of this innovation, one of which is awareness. The awareness of users or local people who use vehicles in traffic, whether land, sea or air, of course they do not have awareness.